Ischemic Diffusion Lesion Reversal After Endovascular Treatment: Prevalence, Prognosis, and Predictors. Issue 6 (June 2019) - Yoo, Joonsang; Choi, Jin Wook; Lee, Seong-Joon; Hong, Ji Man; Hong, Jeong-Ho; Kim, Chang-Hyun; Kim, Yong-Won; Kang, Dong-Hun; Kim, Yong-Sun; Hwang, Yang-Ha; Ovbiagele, Bruce; Demchuk, Andrew M.; et al.
Abstract : Background and Purpose—: Several studies have reported partial reversal of diffusion-weighted imaging (DWI) lesions after acute stroke reperfusion treatment. However, factors associated with DWI reversal have not yet been systematically investigated. We evaluated the factors associated with DWI reversal after endovascular treatment (EVT). Methods—: We retrospectively analyzed consecutively encountered patients with acute ischemic stroke who underwent EVT at 3 comprehensive stroke centers in Korea from January 2011 to February 2016. Patients who received EVT within 24 hours of anterior circulation infarction and had both baseline and follow-up DWIs were included. DWI reversal was defined as a decrease in DWI volume from baseline to follow-up. We compared the characteristics and outcomes between patients with and without DWI reversal and assessed independent factors associated with DWI reversal. Results—: Of 720 patients encountered during the time period, 404 patients (56.1%) met the study criteria, with 63 patients (15.5%) showing DWI reversal after EVT. The mean time interval between baseline and follow-up DWI was 4.7±2.4 days. Mean baseline DWI volumes of patients with and without DWI reversal were 30.1±36.7 versus 22.0±30.7 mL ( P =0.106), and follow-up DWI volumes were 17.8±24.9 versus 68.7±77.5 mL ( P <0.001). Patients with DWI reversal showed better functional outcomes at 3 months than those without DWI reversal (modified Rankin Scale [interquartile range], 1 [0–3] versus 2 [1–4]; P =0.001). In a multivariate analysis, complete reperfusion (odds ratio, 1.954; 95% CI, 1.063–3.582) and shorter time from baseline DWI to final reperfusion (odds ratio, 0.991; 95% CI, 0.983–0.998) were independently associated with DWI reversal. Conclusions—: Complete reperfusion and shorter imaging time to recanalization were independently associated with DWI reversal among patients with acute ischemic stroke who received EVT. Abstract : Supplemental Digital Content is available in the text.